2013
DOI: 10.1016/j.actpsy.2013.05.009
|View full text |Cite
|
Sign up to set email alerts
|

The link between mental rotation ability and basic numerical representations

Abstract: Mental rotation and number representation have both been studied widely, but although mental rotation has been linked to higher-level mathematical skills, to date it has not been shown whether mental rotation ability is linked to the most basic mental representation and processing of numbers. To investigate the possible connection between mental rotation abilities and numerical representation, 43 participants completed four tasks: 1) a standard pen-and-paper mental rotation task; 2) a multi-digit number magnit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 67 publications
(42 reference statements)
5
56
0
5
Order By: Relevance
“…The present findings are potentially informative for the design and implementation of training studies. Previous research highlighted the positive role of spatial skills for basic number processing (Crollen & Noël, 2015;Thompson et al, 2013) and more complex mathematical calculations and/or mathematical expertise (Geary, Saults, Liu, & Hoard, 2000;Sella, Sader, Lolliot, & Cohen Kadosh, 2016;Wei, Yuan, Chen, & Zhou, 2012; see also review by de Hevia, Vallar, & Girelli, 2008). We show that spatial skills, notably mental rotation, are also important for basic arithmetic, especially at the stage of skill acquisition.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The present findings are potentially informative for the design and implementation of training studies. Previous research highlighted the positive role of spatial skills for basic number processing (Crollen & Noël, 2015;Thompson et al, 2013) and more complex mathematical calculations and/or mathematical expertise (Geary, Saults, Liu, & Hoard, 2000;Sella, Sader, Lolliot, & Cohen Kadosh, 2016;Wei, Yuan, Chen, & Zhou, 2012; see also review by de Hevia, Vallar, & Girelli, 2008). We show that spatial skills, notably mental rotation, are also important for basic arithmetic, especially at the stage of skill acquisition.…”
Section: Discussionsupporting
confidence: 49%
“…Symbolic numerical abilities have been consistently reported to be a strong predictor of performances in mathematics (e.g., Sasanguie, Göbel, Moll, Smets, & Reynvoet, 2013;Schneider et al, 2017). In addition, they relate to spatial skills, notably mental rotation (e.g., Thompson et al, 2013). To control for the prominent effect of domain-specific basic symbolic number skills on arithmetic performances and to determine whether mental rotation can explain additional variance especially at the acquisition stage, we included a symbolic magnitude classification task as a control measure in our analyses.…”
Section: Aimmentioning
confidence: 99%
“…This argument of a physically spatial (left-right) differentiation between tens and units is further corroborated by a recent study evaluating the association between place-value processing reflected by the UD compatibility effect and mental rotation. Thompson, Nuerk, Moeller, and Cohen Kadosh (2013) observed that the better participants were able to differentiate tens from units (as indicated by a relatively higher compatibility effect) the better was their mental rotation performance. The authors interpreted this to indicate that being able to process tens and units spatially separated helps to keep track of different features of an object when mentally rotating itwhich clearly emphasises the spatial place aspect of the representation of the place-value structure of Arabic numbers.…”
Section: Embodied and Situated Aspects Of Processing Place-value Infomentioning
confidence: 92%
“…Moreover, memory deficits cause a confusion on mathematic terminology [24], on performing mental calculation [25] and on keeping track on steps on problem solving [26]. Furthermore, several studies suggests [27,28,29] that there is a positive correlation between visual spatial perception and mathematical ability. In other words, children that perform better in spatial tasks, perform better in mathematical tests.…”
Section: Introductionmentioning
confidence: 99%